Business sustainability of medicinal plant production under risk in the northwest region of Bangladesh: A simulation analysis - Md. Abu Saiyem; Mst. Fatema Begum; Mst. Esmat Ara Begum; Mohammad Ismail Hossain (PLoS ONE, 2025)
Medicinal plants (MP) provide an opportunity for profitable farming, agricultural diversification, and sustainable livelihoods in Bangladesh. This study aims to examine the business sustainability of MP production under risks, i.e., price, yield and market absorption. Data were collected from 196 individual farms that cultivate Aloe vera (L), Bombax ceiba (L) root, and Withania somnifera (L). The business viability analysis was carried out by evaluating the net present value (NPV), internal rate of return (IRR), benefit-cost ratio (BCR), return on investment (ROI), and real option value (ROV) of selected MP. The results indicated that the NPV was positive, the BCR was greater than 1, and the IRR exceeded the prevailing bank rate. It also found that the production of MP faces three major risks: pricing, yield, and market absorption. The simulation analysis’s findings indicated that MP producers will eventually experience losses with embedded risks. On the other hand, the ROV finding indicated that NPV increases with option value over time. Farmers may receive profit from their investments in A. vera, B. ceiba root, and W. somnifera, and their farming business will eventually become sustainable in the long run. Thus, farmers should plan for producing MP in the long run and policy should be triggered on tackling risk reduction strategies through introducing marketing contract.